1988
DOI: 10.1038/331530a0
|View full text |Cite
|
Sign up to set email alerts
|

Novel precursor of Alzheimer's disease amyloid protein shows protease inhibitory activity

Abstract: Alzheimer's disease is characterized by cerebral deposits of amyloid beta-protein (AP) as senile plaque core and vascular amyloid, and a complementary DNA encoding a precursor of this protein (APP) has been cloned from human brain. From a cDNA library of a human glioblastoma cell line, we have isolated a cDNA identical to that previously reported, together with a new cDNA which contains a 225-nucleotide insert. The sequence of the 56 amino acids at the N-terminal of the protein deduced from this insert is high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
368
0
5

Year Published

1990
1990
1998
1998

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 1,050 publications
(379 citation statements)
references
References 26 publications
6
368
0
5
Order By: Relevance
“…Proteolytic processing of these APP proteins in the Golgi apparatus leads to the secretion of the extracellular part the APP protein isoforms [8]. proteins differ from APP69s by one or two additional domains of 56 or 56 and 19 amino acids [12]. Both domains are encoded by two adjacent exons on the PAD gene, namely exon 7 (168 bp) and exon 8 (57 bp) [ 12,131.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Proteolytic processing of these APP proteins in the Golgi apparatus leads to the secretion of the extracellular part the APP protein isoforms [8]. proteins differ from APP69s by one or two additional domains of 56 or 56 and 19 amino acids [12]. Both domains are encoded by two adjacent exons on the PAD gene, namely exon 7 (168 bp) and exon 8 (57 bp) [ 12,131.…”
Section: Introductionmentioning
confidence: 99%
“…proteins differ from APP69s by one or two additional domains of 56 or 56 and 19 amino acids [12]. Both domains are encoded by two adjacent exons on the PAD gene, namely exon 7 (168 bp) and exon 8 (57 bp) [ 12,131. The expression of the PAD gene is ubiquitous, being highest in brain and kidney [lo].…”
Section: Introductionmentioning
confidence: 99%
“…The molecularweight-markers used in SDYPAGE were 21 2-kDa myosin. 170-kDa P-galactosidase, 76-kDa transferrin, 53-kDa glutamic dehydrogenase, 33-kDa carbonic anhydrase, 24-kDa soy bean trypsin inhibitor, 16-kDa lysozymc, 14-kDa myoglobin I+II, 8.2-kDa myoglobin I and 3.5-kDa glucagon (Bio Rad. Pharmacia and Sigma).…”
Section: Protein Separation and Analysismentioning
confidence: 99%
“…3, lanes 1,5,9). This heterogeneity has previously been shown to be due to the facts first that the APP hn mRNA is differentially spliced into 3 major mRNA forms [6,9,23], and second that the APP protein is subjected to intracellular processing including Iv-, Oglycosylation, and thyorosine sulfation [I I]. Secretion 'of the major N-terminal part of APP is achieved by proteolytic cleavage of the mature transmembrane APP molecule [12] resulting in secreted APP forms in the molecular weight range between 98 kRa and 123 kDa (Fig.…”
Section: Malerialsmentioning
confidence: 99%
“…Proteases and their inhibitors may contribute to pathogenic events. In Alzhcimer's disease (AD), proteases and their inhibitors seem to be of particular importance: (i) the proteases cathepsin B and D [4] as well as the proteinase inhibitor alpha I-antichymotrypsin [S] have been found to be constituents of AD senile plaques; (ii) two forms (APP751 and the APPvo) of the Alzheimer @G4-amyloid precursor protein (APP) are Kunitz-type proteinase inhibitors [6,7, for reviews see 7,8]; (iii) by investigating APP synthesis in cultured cells it has been found that secretion of (the large N-terminal part of) APP is the result of a proteolytic cleavage C-terminal to residue 16 of the @A4 part of the mature transmembrane APP [g-13]. mation of AD senile plaques 1321.…”
Section: Introductioi\imentioning
confidence: 99%